(untitled) (Jahangirnagar University Journal of Biological Sciences, 2020)
The prevalence of ectoparasitic arthropods of cattle and goats in Daudkandi, Homna and Titas upazilas of Comilla district were investigated. During this study (December 2013 to November 2014) 299 cattle and 196 goats were examined; and among them 180 and 117 were found to be infested respectively. Seventeen species of ectoparasites (both larvae and adult) were identified and they are Haematopinus quadripertusus, Haematopinus eurysternus, Linognathus vituli, Damalinia bovis, Stomoxys calcitrans, Musca domistica, Tabanus striatus, Diachlorus sp., Armigeres subalbatus, Ctenocephalides felis, Boophilus microplus, Haemaphysalis bispinosa, Haemaphysalis kinneari, Hyalomma anatolicum, Rhipicephalus sanguineus, Dermacentor sp. and Ixodes sp. The highest prevalence of ectoparasitic infestation (69.94%) were found in Titas and the lowest (53.34%) in Homna upazila. The intensity of ectoparasitic infestation was highest in Titas (12.20) and lowest in Homna (5.21) upazila. Cattle in Titas upazila showed highest prevalence (67.53%) and intensity (8.04) and Homna upazila showed lowest prevalence (48.63%) and intensity (5.55). Goats in Titas upazila showed highest prevalence (76.09%) and intensity (8.38), and Daudkandi upazila showed lowest prevalence (49.37%) and goats in Homna showed lowest intensity (4.80). This study quantifies the level of ectoparasitic infestation in cattle and goats which demands immediate control program and needs more intensive epidemiological study for detail identification of the constraints of animal health and production. Jahangirnagar University J. Biol. Sci. 8(2): 35-45, 2019 (December)